AN ADDITIONAL SPECIES OF VILLARIA ROLFE (RUBIACEAE) FROM THE PHILIPPINES - Tri Mulyaningsih; Colin Ernest Ridsdale (REINWARDTIA, 2004)
MULYANINGSIH, TRI & RIDSDALE, COLIN ERNEST. 2004. An additional species of Villaria Rolfe (Rubiaceae) from the Philippines. Reinwardtia 12 (2): 195 – 197. A new combination of Villaria Rolfe (Rubiaceae) from the Philippines is described, based on Hypobathrum glomeratum (Bartl.) K. Schum. The character combinations of stipules, bracts, bracteoles, calyx, ovary and placenta seen in this taxon are not found in Hypobathrum but are known in Villaria.